Corrosion and hydrogen pickup mechanisms of zirconium alloys - Setiadinata, SB (2016)
Zirconium alloy cladding isolates the nuclear fuel rods from water coolant in a nuclear fission reactor, but in this harsh environment experience high temperature aqueous corrosion and hydrogen pickup (HPU). The segregation of minor elements such as iron, niobium and antimony greatly affects the corrosion and HPU of Zr alloys, but often this segregation occurs at a scale too small for most characterisation techniques to observe. Atom probe tomography (APT) enables the 3D analysis of elemental distributions on the atomic scale using time-of-flight spectroscopy. .